ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA PADA RUMAH YATIM DAN TAHFIDZ QUR’AN MADANI - Willy Hardian; Dicky Maryono (UM. Bengkulu, 2026)
This study discusses the analysis of human resource management (HR) in the institution of Rumah Tahfidz Qur'an Madani, including knowing the problems and impacts of human resource development in the Rumah Yatim and Tahfidz Qur'an Madani. The research method used is a qualitative descriptive method, the stages of research are by conducting field observations, interviews and documentation. The results of the research obtained are that the development of human resources at the Madani Orphanage and Qur'an is quite good, the Madani Orphanage and Qur'an Madani institution provides development training to teaching staff, namely by holding soft skills and hard skills development training such as public speaking training, writing training, English courses and others. The impact obtained from the results of the analysis are: Improving the Quality of Teaching, Developing Soft Skills. The challenges faced when providing development training include: Limited resources, need for continuous training and financial limitations. Keywords: development, HR.